The involvement of Neuregulin-1 in the process of facial nerve injury repair through the utilization of dental pulp stem cells - Lihong Yao; Wanqiu Xu; Lixue Liu; Xiaohang Xu; Hualei Xi; Bing Xue; Xiaofang Cao; Song Lin; Guiyan Piao; Jian Sun; Xiumei Wang (BMC, 2024)
Abstract Background Facial nerve injury often results in poor prognosis due to the challenging process of nerve regeneration. Neuregulin-1, a human calmodulin, is under investigation in this study for its impact on the reparative capabilities of Dental Pulp Stem Cells (DPSCs) in facial nerve injury. Methods Lentivirus was used to transfect and construct Neuregulin-1 overexpressed DPSCs. Various techniques assessed the effects of Neuregulin-1: osteogenic induction, lipid induction, Reverse Transcription Polymerase Chain Reaction, Western Blot, Cell Counting Kit-8 assay, wound healing, immunofluorescence, Phalloidin staining, nerve stem action potential, Hematoxylin-eosin staining, transmission electron microscopy, and immunohistochemistry. Results Neuregulin-1 effectively enhanced the proliferation, migration, and cytoskeletal rearrangement of DPSCs, while simultaneously suppressing the expression of Ras homolog gene family member A (RhoA) and Microfilament actin (F-actin). These changes facilitated the neural differentiation of DPSCs. Additionally, in vivo experiments showed that Neuregulin-1 expedited the restoration of action potential in the facial nerve trunk, increased the thickness of the myelin sheath, and stimulated axon regeneration. Conclusion Neuregulin-1 has the capability to facilitate the repair of facial nerve injuries by promoting the regenerative capacity of DPSCs. Thus, Neuregulin-1 is a significant potential gene in the reparative processes of nerve damage.